ANALISIS DAYA SAING CRUDE PALM OIL (CPO) INDONESIA DI PASAR INTERNASIONAL - RASHID ANGGIT Y.A.D; NI MADE SUYASTIRI Y.P; ANTIK SUPRIHANTI (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2012)
This study aims to analyze export volume trend of Indonesian CPO in International market for the next 3 years and to analyze competitiveness of Indonesian crude palm oil in International market. To analyze the competitiveness of Indonesian crude palm oil in International market used Revealed Comparative Advantage analysis (RCA) to analyze comparative advantage and Trade Specialization Index (ISP) to analyze competitive advantage. Mean while, to analyze the export volume of Indonesian crude palm oil in the international market for next 3 years used least squares method.